As-cast b2 phase+l21 phase strengthened ferrite-based superalloy and improvement method

CN122898706APending Publication Date: 2026-10-13UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明提供了一种铸态B2相+L21相强化铁素体基超合金及提升方法,以克服现有技术中该类合金大重量铸锭(100-1000公斤级)铸态组织粗大、脆性高、难以开坯等问题,并解决相关潜在缺陷

Benefits of technology

1、本发明针对B2相+L21相强化铁素体基合金在双联工艺制备大尺寸铸锭过程中易形成粗大晶粒、塑性差及开坯易开裂的问题,通过循环热处理实现铸态组织重构,显著细化晶粒并提高组织均匀性,从而有效降低开裂倾向,提升开坯成形能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898706A_ABST
    Figure CN122898706A_ABST
Patent Text Reader

Abstract

The application discloses a kind of as-cast B2 phase+L21 phase reinforced ferrite-based superalloy and promotion method, the method comprises: using vacuum induction melting is combined with electroslag remelting to prepare as-cast ferrite-based alloy ingot;After eliminating dendritic segregation by high-temperature homogenization treatment, ferrite / austenite dual-phase zone cyclic heat treatment is carried out, so that the alloy occurs multiple reversible phase transformation between ferrite and austenite;Subsequently, high-temperature forging is carried out to obtain a macro-crack-free blank, and a B2 phase+L21 phase reinforced ferrite-based superalloy is obtained by two-stage aging treatment.The application realizes grain refinement and organization homogenization by cyclic phase transformation control of as-cast coarse organization, significantly improves the plasticity and hot working performance of the alloy, solves the problem of coarse as-cast organization, high brittleness and difficult to break down of the alloy, and has good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hot working and heat treatment technology of metallic materials, and specifically relates to a cast B2 phase + L21 phase strengthened ferrite-based superalloy and its enhancement method. Background Technology

[0002] Ferrite-based alloys possess advantages such as low cost, low coefficient of thermal expansion, high strength, and excellent oxidation resistance, demonstrating significant application potential in the field of high-temperature structural materials. The B2 phase (β′) is an ordered body-centered cubic (BCC) intermetallic compound that can form a coherent interface with low lattice mismatch with the ferrite matrix, thus establishing a stable interfacial bond at the crystallographic level. This "α-β′" two-phase microstructure is similar in mechanism to the γ-γ′ strengthening system in nickel-based superalloys, significantly improving the alloy's strength, creep resistance, and high-temperature structural stability. Therefore, this type of material is also referred to by some researchers as ferrite-based superalloys. Furthermore, by introducing alloying elements such as Ti and Hf into the alloy system, the B2 phase can undergo ordered structural evolution and transform into an L21-type Heusler structure, thereby forming a composite precipitate phase system where B2 and L21 coexist. When the precipitated phase is controlled from a single B2 phase to a B2-L21 composite structure, its structural stability and anti-coarsening ability at high temperatures are further enhanced, while its hindering effect on dislocation movement becomes more significant, thereby significantly improving the high-temperature creep resistance of the material. Therefore, the synergistic precipitation and structural control of the B2 and L21 phases is an important technical path to achieve high performance of ferrite-based superalloys.

[0003] However, existing research has shown that while the introduction of the L21 phase improves high-temperature performance, it often significantly reduces the intrinsic plasticity of ferritic alloys (Journal of Materials Research and Technology, 2023, 25:3273-3284). Furthermore, in actual industrial manufacturing processes, especially under the solidification conditions of large ingots of 100 kg and above, limited heat dissipation easily leads to the formation of coarse dendritic or columnar crystal structures within the alloy, accompanied by severe elemental segregation and non-uniform grain boundary composition. During subsequent billeting or forging processes, strain is difficult to uniformly transfer between the coarse grains, and localized stress tends to concentrate at grain boundaries, segregation zones, and phase interfaces, thus inducing intergranular cracking or even overall failure, severely impacting the yield of large ingots.

[0004] Existing technologies typically employ large plastic deformation processes (such as multi-stage forging or high-compression-ratio rolling) to break down the as-cast microstructure and achieve grain refinement and microstructure reconstruction through dynamic recrystallization (DRX) mechanisms, thereby improving the microstructure of the material. However, for B2+L21 co-strengthened ferrite-based superalloys, due to the high brittleness of the as-cast microstructure and the large resistance to high-temperature deformation, such methods often suffer from problems such as a narrow process window, high equipment requirements, and the tendency for cleavage fracture to induce macroscopic cracking in the ingot during deformation. Therefore, there is an urgent need for a new method that does not rely on external large plastic deformation and can utilize the internal phase transformation driving force of the material to achieve microstructure reconstruction and plasticity improvement, in order to solve the technical problem of brittle cracking that easily occurs during the large-size ingot blanking process of this type of alloy. Summary of the Invention

[0005] This invention provides a cast B2 phase + L21 phase strengthened ferrite-based superalloy and its improvement method to overcome the problems of large weight ingots (100-1000 kg) of this type of alloy in the prior art, such as coarse as-cast microstructure, high brittleness, and difficulty in billet making, and to solve related potential defects.

[0006] The method of the present invention includes the following steps: A method for improving the plasticity and machinability of as-cast B2 phase + L21 phase strengthened ferrite matrix superalloys includes the following steps: (1) High-purity raw materials were used to prepare as-cast B2 phase + L21 phase reinforced ferrite-based alloy ingots by a dual process of vacuum induction melting and electroslag remelting. (2) High-temperature homogenization treatment was performed on the as-cast B2 phase + L21 phase reinforced ferrite-based alloy ingot; (3) The alloy obtained after homogenization is subjected to several cycles of heat treatment to obtain a fully austenitic alloy. (4) After the last cycle is completed, the alloy is cooled to room temperature and forged to obtain a forged alloy without macroscopic cracking. (5) The forged alloy was subjected to a two-stage aging treatment to obtain a B2 phase + L21 phase reinforced ferrite-based superalloy.

[0007] In addition to the aspects described above and any possible implementation, a further implementation is provided in which the chemical composition of the alloy ingot in step (1) is: Fe: 9-13 wt.%, Cr: 3-6 wt.%, Al: 10-18 wt.%, Co: 10-15 wt.%, Ni: 0-3 wt.%, Mo: 0-3 wt.%, W: 0.5-3 wt.%, Ti: 0.02-0.3 wt.%, Nb: 0.002-0.03 wt.%, B: 0.03-0.1 wt.%, with the remainder being C.

[0008] In addition to the aspects and any possible implementations described above, a further implementation is provided in which the homogenization temperature in step (2) is 1100-1300℃, the holding time is 6-24 hours, and the cooling method is air cooling.

[0009] In addition to the aspects and any possible implementations described above, a further implementation is provided in which the number of cycles is 1-5 times, each cycle being the same, and each cycle comprising: holding at a temperature range of 650-900°C to completely transform the alloy obtained after homogenization treatment into a ferritic alloy; and then heating to 1000-1200°C to completely austenitize the ferritic alloy.

[0010] In addition to the aspects and any possible implementations described above, a further implementation is provided in which the heat preservation time at 650-900℃ in step (3) is 24-72 hours and the heat preservation time at 1000-1200℃ is 30-90 minutes.

[0011] In addition to the aspects and any possible implementations described above, an implementation is further provided in which the initial forging temperature in step (4) is 900-1000℃, the final forging temperature is 800-900℃, and the relative deformation is 50%-66%.

[0012] In addition to the aspects and any possible implementations described above, an implementation is further provided in which the two-stage aging process in step (5) includes: the first aging temperature is 800-950℃ and the time is 1-3 hours; The second step involves aging at a temperature of 500-760℃ for 12-120 hours.

[0013] In addition to the aspects described above and any possible implementation, a further implementation is provided in which the aging temperature in the second step is 550-700℃ and the time is 24-72 hours.

[0014] In addition to the aspects described above and any possible implementation, a further implementation is provided in which the purity of the high-purity raw material is 99.9% or higher.

[0015] The present invention also discloses an as-cast B2 phase + L21 phase reinforced ferrite-based superalloy, which is obtained by the method described above.

[0016] Beneficial effects: 1. This invention addresses the problems of coarse grains, poor plasticity, and easy cracking during the preparation of large-size ingots in B2 phase + L21 phase reinforced ferrite-based alloys using a duplex process. By reconstructing the as-cast microstructure through cyclic heat treatment, the grains are significantly refined and the microstructure uniformity is improved, thereby effectively reducing the tendency to crack and improving the billet forming ability.

[0017] 2. This invention utilizes the cyclic phase transformation in the ferrite / austenite dual-phase region to achieve grain refinement and microstructure homogenization under conditions without large plastic deformation, breaking through the limitations of traditional processes that rely on heavy deformation, and forming a new method for microstructure control with phase transformation as the core.

[0018] 3. This invention, through compositional design, coordinates the proportions of elements such as Cr, Al, Co, Mo, W, Ti, and Nb to ensure ferrite stability in the mid-temperature zone and complete austenitization in the high-temperature zone. It also regulates the B2 / L21 precipitation kinetics and, in conjunction with the cyclic heat treatment process, achieves a refined and uniform microstructure while constructing a high-density effective nucleation interface and realizing the stable precipitation of high-volume-fraction B2 and L21 phases. This balances the improvement of material plasticity and strengthening effect, significantly improving comprehensive mechanical properties and processing adaptability. Attached Figure Description

[0019] Figure 1 This is a process flow diagram of the present invention; Figure 2 The images show the inverse pole figures obtained by electron backscatter diffraction (EBSD) analysis before and after the cyclic heat treatment experiment of this invention. (a) is the inverse pole figure before the experiment; and (b) is the inverse pole figure after the experiment. Detailed Implementation

[0020] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0021] It should be noted that the terms "comprising" and "having" and any variations thereof in the specification, claims and accompanying drawings of this invention are intended to cover non-exclusive inclusion. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such processes, methods, products or devices.

[0022] like Figure 1 As shown, this invention provides a method for improving the plasticity and machinability of as-cast B2 phase + L21 phase strengthened ferrite-based superalloys through cyclic heat treatment, comprising the following steps: (1) High-purity raw materials are selected, and a dual process of vacuum induction melting combined with electroslag remelting is adopted to prepare cast ferritic alloy ingots. The chemical composition of the alloy ingots is as follows: Fe: 9-13 wt.%, Cr: 3-6 wt.%, Al: 10-18 wt.%, Co: 10-15 wt.%, Ni: 0-3 wt.%, Mo: 0-3 wt.%, W: 0.5-3 wt.%, Ti: 0.02-0.3 wt.%, Nb: 0.002-0.03 wt.%, B: 0.03-0.1 wt.%, with the remainder being C; (2) The as-cast B2 phase + L21 phase reinforced ferrite-based alloy ingot obtained in step (1) is subjected to high-temperature homogenization treatment to eliminate dendrite segregation. The homogenization treatment temperature is 1100-1300℃, the holding time is 6-24 hours, preferably 6-12 hours, and the cooling method is air cooling. Under this condition, the degree of dendrite segregation is greatly reduced, the composition inhomogeneity is significantly reduced, and local abnormal structures are avoided in the subsequent phase transformation process. (3) The homogenized alloy is subjected to cyclic heat treatment, wherein each cycle includes: holding at a temperature range of 650-900℃ for 24-72 hours to completely transform the alloy matrix into ferrite; then raising the temperature to 1000-1200℃ and holding for 30-90 minutes to completely austenitize the alloy; this temperature and time range ensures that the phase transformation is fully carried out, avoiding both excessively long time leading to coarse grains and excessively short time leading to incomplete transformation; after repeating 1-5 cycles, the original coarse grains are gradually refined, such as Figure 2 As shown, the inverse pole figures obtained by electron backscatter diffraction (EBSD) analysis before and after the cyclic heat treatment experiment are shown in the following: (a) is the inverse pole figure before the experiment, which shows that the original cast structure has coarse grains, disordered orientation distribution, and obvious dendritic segregation; (b) is the inverse pole figure after the experiment, which shows that the grains are significantly refined after cyclic heat treatment. (4) After the last cycle is completed, the alloy is cooled to room temperature and forged to obtain a billet without macroscopic cracking. The standard for no macroscopic cracking is that there are no visible cracks on the surface of the billet and no linear defects are detected by dye penetration testing, ensuring that the billet can be used for subsequent processing without breaking. The initial forging temperature is 900-1000℃, the final forging temperature is 800-900℃, and the relative deformation is 50%-66%. In this temperature range, the alloy is in the austenite or two-phase region, with sufficient plasticity. With a larger deformation, the grains can be further refined and the internal micropores can be closed to improve the density. (5) The forged alloy was subjected to a two-stage aging treatment to obtain a B2 phase + L21 phase reinforced ferrite-based superalloy.

[0023] The two-stage aging process includes: the first stage aging temperature is 800-950℃, and the time is 1-3 hours; The second aging process involves an aging temperature of 500-760℃, preferably 550-700℃, for 12-120 hours, preferably 24-72 hours. This two-stage aging process allows the B2 phase to first nucleate uniformly at high temperature, and then partially transform into the L21 structure at low temperature, ultimately obtaining coexisting two phases with fine-sized precipitate particles, with a volume fraction of 30%-50%, significantly improving the alloy strength without losing too much plasticity.

[0024] This invention proposes a method for grain refinement and alloy plasticity improvement based on cyclic heat treatment. Cyclic heat treatment, as a microstructure control method based on repeated solid-state phase transformation, can achieve continuous nucleation and growth of new phases through the periodic phase transformation process between ferrite and austenite without the need for external plastic deformation. This continuously segments and reconstructs the original coarse as-cast grains. With the increase of the number of cycles, a large number of new grains nucleate simultaneously and compete for growth space, thereby inhibiting abnormal grain growth. Ultimately, the coarse as-cast microstructure gradually transforms into a fine and uniform polycrystalline microstructure, achieving microstructure refinement and significant improvement in plasticity. This method provides the basic process path for achieving as-cast microstructure reconstruction and plasticity improvement in this invention.

[0025] The method of this invention is not only reflected in the process path design, namely, replacing traditional large plastic deformation with a two-phase cyclic phase transformation to achieve the transformation from a highly brittle as-cast microstructure to a highly plastic processing microstructure, but also in the synergistic optimization design of the alloy system's phase transformation thermodynamics and kinetics. Specifically, the resulting alloy system has the following advantages: (1) After the final aging treatment, the volume fraction of B2 phase and L21 phase precipitate reaches 30%-50%. This effect is guaranteed by the process parameters of the two-stage aging in step (5) combined with the content of Al, Ti and Nb in the aforementioned components. Specifically, the full analysis is achieved by controlling the aging temperature and time. (2) The alloy matrix can be stably converted into a single ferrite (α-Fe) structure in the medium temperature range (600-850℃) of the cyclic heat treatment, and a large number of B2 / α-Fe and L21 / α-Fe interfaces are formed. This condition is guaranteed by the composition design in step (1). In particular, elements such as Cr, Co, and Mo improve the stability of ferrite, while elements such as Al and Ti promote the nucleation of B2 / L21. This makes the matrix ferrite in this temperature range and rich in precipitated phase interfaces, providing favorable positions for subsequent austenite nucleation. These interface regions can achieve the compositional fluctuation conditions for austenite nucleation and serve as non-uniform nucleation sites for high-temperature austenite (γ-Fe). (3) It can be completely transformed into austenite (γ-Fe) structure in the high temperature range (1000-1200℃) of the cyclic heat treatment. This advantage is also guaranteed by the composition design. By reducing the content of austenite stabilizing elements such as Ni and Mn and increasing the content of ferrite stabilizing elements such as Al and Cr, the austenite phase region is moved up to above 1000℃, ensuring that there is no residual ferrite at this temperature, achieving complete phase transformation, and the precipitated phase is completely dissolved, with no residual α-Fe in the matrix.

[0026] Based on the above design, this invention utilizes a cyclic phase transformation process driven primarily by thermodynamics to effectively reconstruct the coarse microstructure in the as-cast state, eliminating the inherited characteristics of the as-cast microstructure and weak regions with brittle grain boundaries, thereby establishing a synergistic mechanism of "phase transformation regulation - plasticity enhancement - billet performance optimization". This method fundamentally overcomes the technical bottleneck of easy brittle fracture during the billet-making process of B2 phase + L21 phase strengthened ferrite-based superalloys, demonstrating significant technological advancement and promising industrial application prospects.

[0027] The following specific examples illustrate this.

[0028] Example 1:

[0029] High-purity raw materials with a purity of not less than 99.9 wt.% were selected, and a cast ferritic alloy ingot with the composition of Fe-10%Cr-4%Al-12%Co-1%Ni-1%Mo-1%W-0.1%Ti-0.01%Nb-0.05%BC (mass percentage) was prepared using a dual process of vacuum induction melting combined with electroslag remelting. The cast alloy ingot was homogenized at 1200℃ for 10 hours to reduce the influence of dendrite segregation, followed by air cooling. The homogenized alloy underwent cyclic heat treatment for a total of 3 cycles. Each cycle included: holding at 750℃ in the ferritic single-phase region for 48 hours to completely transform the alloy into a ferritic structure; then heating to 1100℃ and holding for 60 minutes to completely austenitize the alloy, followed by air cooling. The cyclically heat-treated alloy was initially forged at 950℃ and finally forged at 850℃, with a relative deformation of 60%, yielding a forged billet without macroscopic cracking. The forged alloy was then subjected to a two-stage aging treatment. The first step involved holding at 850℃ for 2 hours and then air cooling. The second step involved holding at 650℃ for 48 hours and then air cooling, ultimately yielding a B2 phase + L21 phase reinforced ferrite-based superalloy.

[0030] Example 2:

[0031] High-purity raw materials with a purity of not less than 99.9 wt.% were selected, and a cast ferritic alloy ingot with the composition of Fe-12%Cr-5%Al-15%Co-2%Ni-1%Mo-2%W-0.2%Ti-0.02%Nb-0.06%BC (mass percentage) was prepared using a dual process of vacuum induction melting combined with electroslag remelting. The cast alloy ingot was homogenized at 1250℃ for 8 hours to reduce the influence of dendrite segregation, followed by air cooling. The homogenized alloy underwent cyclic heat treatment, consisting of two cycles. Each cycle included: holding at 800℃ in the ferritic single-phase region for 36 hours to completely transform the alloy into a ferritic structure; then heating to 1150℃ and holding for 45 minutes to completely austenitize the alloy, followed by air cooling. The cyclically heat-treated alloy was initially forged at 980℃ and finally forged at 880℃, with a relative deformation of 55%, yielding a forged billet without macroscopic cracking. The forged alloy was then subjected to a two-stage aging treatment. The first step involved holding at 900℃ for 1.5 hours and then air cooling. The second step involved holding at 700℃ for 36 hours and then air cooling, ultimately yielding a B2 phase + L21 phase reinforced ferrite-based superalloy.

[0032] Example 3:

[0033] High-purity raw materials with a purity of not less than 99.9 wt.% were selected, and a cast ferritic alloy ingot with the composition of Fe-9%Cr-3%Al-10%Co-0%Ni-0%Mo-0.5%W-0.05%Ti-0.005%Nb-0.04%BC (mass percentage) was prepared using a dual process of vacuum induction melting combined with electroslag remelting. The cast alloy ingot was homogenized at 1150℃ for 12 hours to reduce the influence of dendrite segregation, followed by air cooling. The homogenized alloy was then subjected to cyclic heat treatment for a total of 4 cycles. Each cycle included: holding at 700℃ in the ferrite single-phase region for 60 hours to completely transform the alloy into a ferrite structure; then heating to 1050℃ and holding for 75 minutes to completely austenitize the alloy, followed by air cooling. The alloy after cyclic heat treatment was initially forged at 920℃ and finally forged at 820℃, with a relative deformation of 65%, resulting in a forged billet without macroscopic cracking. The forged alloy was then subjected to a two-stage aging treatment: first, holding at 820℃ for 3 hours followed by air cooling; second, holding at 600℃ for 72 hours followed by air cooling, ultimately yielding a B2 phase + L21 phase strengthened ferrite-based superalloy.

[0034] Example 4:

[0035] High-purity raw materials with a purity of not less than 99.9 wt.% were selected, and a cast ferritic alloy ingot with the composition of Fe-11%Cr-6%Al-13%Co-3%Ni-3%Mo-3%W-0.25%Ti-0.025%Nb-0.08%BC (mass percentage) was prepared using a dual process of vacuum induction melting combined with electroslag remelting. The cast alloy ingot was homogenized at 1300℃ for 6 hours to reduce the influence of dendrite segregation, followed by air cooling. The homogenized alloy underwent cyclic heat treatment, consisting of one cycle. Each cycle included: holding at 850℃ in the ferritic single-phase region for 72 hours to completely transform the alloy into a ferritic structure; then heating to 1200℃ and holding for 30 minutes to completely austenitize the alloy, followed by air cooling. The cyclically heat-treated alloy was initially forged at 1000℃ and finally forged at 900℃, with a relative deformation of 50%, yielding a forged billet without macroscopic cracking. The forged alloy was then subjected to a two-stage aging treatment. The first step involved holding at 950℃ for 1 hour and then air cooling. The second step involved holding at 550℃ for 120 hours and then air cooling, ultimately yielding a B2 phase + L21 phase reinforced ferrite-based superalloy.

[0036] As an embodiment of the present invention, the present invention also provides a cast B2 phase + L21 phase reinforced ferrite-based superalloy, which is obtained by the method described above.

[0037] The foregoing description illustrates and describes several preferred embodiments of the present invention. However, as previously stated, it should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the inventive concept described herein through the foregoing teachings or techniques or knowledge in related fields. Any modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A method for enhancing the strength of as-cast B2 phase + L21 phase ferrite-based superalloys, characterized in that, Includes the following steps: (1) High-purity raw materials were used to prepare as-cast B2 phase + L21 phase reinforced ferrite-based alloy ingots by a dual process of vacuum induction melting and electroslag remelting. (2) High-temperature homogenization treatment was performed on the as-cast B2 phase + L21 phase reinforced ferrite-based alloy ingot; (3) The alloy obtained after homogenization is subjected to several cycles of heat treatment to obtain a fully austenitic alloy. (4) After the last cycle is completed, the alloy is cooled to room temperature and forged to obtain a forged alloy without macroscopic cracking. (5) The forged alloy was subjected to a two-stage aging treatment to obtain a B2 phase + L21 phase reinforced ferrite-based superalloy.

2. The method according to claim 1, characterized in that: The chemical composition of the alloy ingot mentioned in step (1) is as follows: Fe: 9-13 wt.%, Cr: 3-6 wt.%, Al: 10-18 wt.%, Co: 10-15 wt.%, Ni: 0-3 wt.%, Mo: 0-3 wt.%, W: 0.5-3 wt.%, Ti: 0.02-0.3 wt.%, Nb: 0.002-0.03 wt.%, B: 0.03-0.1 wt.%, with the remainder being C.

3. The method according to claim 1, characterized in that: In step (2), the homogenization temperature is 1100-1300℃, the holding time is 6-24 hours, and the cooling method is air cooling.

4. The method according to claim 1, characterized in that: The number of cycles is 1-5 times, and each cycle is the same. Each cycle includes: holding at a temperature range of 650-900℃ to completely transform the alloy obtained after homogenization into a ferritic alloy; and then raising the temperature to 1000-1200℃ to completely austenitize the ferritic alloy.

5. The method according to claim 4, characterized in that: In step (3), the heat preservation time at 650-900℃ is 24-72 hours, and the heat preservation time at 1000-1200℃ is 30-90 minutes.

6. The method according to claim 1, characterized in that: In step (4), the initial forging temperature is 900-1000℃, the final forging temperature is 800-900℃, and the relative deformation is 50%-66%.

7. The method according to claim 1, characterized in that, The two-stage aging process in step (5) includes: the first aging temperature is 800-950℃ and the time is 1-3 hours; the second aging temperature is 500-760℃ and the time is 12-120 hours.

8. The method according to claim 7, characterized in that, The second step involves aging at a temperature of 550-700℃ for 24-72 hours.

9. The method according to claim 1, characterized in that, The purity of the high-purity raw materials is above 99.9%.

10. A cast-state B2 phase + L21 phase reinforced ferrite-based superalloy, characterized in that, The alloy is obtained by the method described in any one of claims 1-9.